Prehistoric Europe (Chichester, U.K.)
xiv, 378 sayfa
Keywords: “Prehistoric Europe: Theory and Practice provides a comprehensive overview of the wide-ranging contemporary debates in the study of European prehistory. Written to reflect the immense changes in the field, the volume presents essays by some of the most dynamic researchers and leading European scholars in the field today. Ranging from the Neolithic period to the early stages of the Iron Age, and from Ireland and Scandinavia to the Urals and the Iberian Peninsula, the book offers a truly contemporary approach to the ever-evolving study of European prehistory.” --